Preoperative albumin-bilirubin grade combined with sarcopenia predicts long-term outcomes after laparoscopic gastrectomy for advanced gastric cancer - Shuangshuang Hou; Yang Yu; Nanbo Li; Wenjing Yu; Zhiyuan Dai; He Li; Lianyi Guo; Jiajun Yin; Ju Wu (BMC Gastroenterology)
Abstract Background This retrospective study evaluated the predictive value of preoperative albumin–bilirubin (ALBI) grade combined with sarcopenia for the long-term prognosis of patients with advanced gastric cancer (AGC) undergoing laparoscopic radical surgery. Methods This study analyzed clinical and pathological data from 731 patients who underwent laparoscopic gastrectomy for AGC in 2011–2019. The training and validation datasets comprised 538 and 193 cases, respectively. Preoperative serum albumin and bilirubin levels were measured to calculate the ALBI score. Sarcopenia was evaluated using the Skeletal Muscle Index (SMI) calculated from preoperative computed tomography images. A new predictive index, s-ALBI, was then established by fitting ALBI and SMI. s-ALBI-1 was defined as low ALBI with no sarcopenia, s-ALBI-2 as low ALBI with sarcopenia or high ALBI with no sarcopenia, and s-ALBI-3 as high ALBI with sarcopenia. Kaplan-Meier survival analysis was used to compare the overall survival (OS) and recurrence-free survival (RFS) of patients in different groups. Univariate and multivariate Cox regression analyses were performed to identify independent risk factors. The predictive ability was assessed using receiver operating characteristic curves and the area under the curve (AUC), followed by external validation. Results The 5-year OS and RFS differed significantly between s-ALBI groups (OS: s-ALBI-1 vs. s-ALBI-2 vs. s-ALBI-3: 77.1% vs. 45.0% vs. 28.4%; RFS: s-ALBI-1 vs. s-ALBI-2 vs. s-ALBI-3: 67.9% vs. 38.5% vs. 24.8%, all P < 0.0001). Moreover, s-ALBI was an independent risk factor for the long-term prognosis of patients with AGC, with modest predictive performance for 5-year OS (AUC = 0.672) and RFS (AUC = 0.648). These results were further confirmed in the external validation set. Conclusions s-ALBI demonstrated modest predictive performance for long-term prognosis in patients with AGC undergoing laparoscopic gastrectomy. Preoperative risk stratification using s-ALBI may help guide personalized treatment plans and optimize therapeutic decision-making.